Communal conflicts and women’s victimization: Women’s victimization depicted in Ice-Candy-Man (1989), A War Heroine, I Speak (2017) And Rohingya: The Sold Dream (2017) - Mou, Anika Tabussum (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in Teaching to Speakers of Other Languages, 2021.